2003
DOI: 10.1021/bp025638o
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Glutamine Fed‐Batch Cultures of 293‐HEK Serum‐Free Suspension Cells for Adenovirus Production

Abstract: Recent developments in gene therapy using adenoviral (Ad) vectors have fueled renewed interest in the 293 human embryonic kidney cell line traditionally used to produce these vectors. Low-glutamine fed-batch cultures of serum-free, suspension cells in a 5-L bioreactor were conducted. Our aim was to tighten the control on glutamine metabolism and hence reduce ammonia and lactate accumulation. Online direct measurement of glutamine was effected via a continuous cell-exclusion system that allows for aseptic, cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 43 publications
3
41
1
1
Order By: Relevance
“…At the process level, the apparent deregulation of glucose and glutamine uptake rates when these nutrients are present in excess has led to the implementation of controlled feeding strategies to maintain low but non-limiting levels of the main nutrient concentrations (Europa et al, 2000;Gambhir et al, 1999;Kurokawa et al, 1994;Lee et al, 2003;Haggstrom, 1992, 1994;Omasa et al, 1992aOmasa et al, , 1992bSiegwart et al, 1999;Zhou et al, 1995). Such strategies have proven effective at reducing the overall yield of lactate on glucose, but require on-line monitoring of nutrient concentrations and automatic feed rate adjustment during the culture.…”
Section: Introductionmentioning
confidence: 99%
“…At the process level, the apparent deregulation of glucose and glutamine uptake rates when these nutrients are present in excess has led to the implementation of controlled feeding strategies to maintain low but non-limiting levels of the main nutrient concentrations (Europa et al, 2000;Gambhir et al, 1999;Kurokawa et al, 1994;Lee et al, 2003;Haggstrom, 1992, 1994;Omasa et al, 1992aOmasa et al, , 1992bSiegwart et al, 1999;Zhou et al, 1995). Such strategies have proven effective at reducing the overall yield of lactate on glucose, but require on-line monitoring of nutrient concentrations and automatic feed rate adjustment during the culture.…”
Section: Introductionmentioning
confidence: 99%
“…In standard cell culture media cell densities in the range 1-4 x 10 6 cells/mL have reached (Lee et al, 2003;Merten, 1987;Ozturk and Palsson, 1990a). In other studies, significantly higher cell densities of >10 7 cells/mL have been reported to be achieved for hybridoma cells (Jo et al, 1993).…”
Section: Batch Culturementioning
confidence: 86%
“…The cells were cultured in 5L bioreactor (B. Braun, Melsungen, Germany) with working volume of 4 l culture medium (HyQ CHO MPS medium from Hyclone, Logan, UT, USA). Fed batch operation was performed using a modified online dynamic feeding strategy as described by Lee et al (2003). Details of fed batch and set-point control operations can be found in the published work of Chee et al (2005).…”
Section: Cell Lines and Culturesmentioning
confidence: 99%